1990
DOI: 10.1080/07448481.1990.9936189
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the Continuum of Self-Destructive Behavior

Abstract: Suicide and self-destructive behavior are strongly influenced by a negative thought process, referred to here as the "voice." The voice process represents a well-integrated pattern of thoughts, attitudes, and beliefs, antithetical to self and hostile toward others, that is at the core of a patient's self-limitations and self-defeating actions. The voice varies along a continuum of intensity ranging from mild self-criticism to angry self-attacks and even suicidal thoughts. Self-destructive behavior similarly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Quantitative investigations of the selfcriticism-DE relation began in the 1970s using small samples from clinical and community settings in the United States (Lehman & Rodin, 1989). Research accelerated after 2000 and found support for the relation of these constructs in adolescents (e.g., Berghold & Lock, 2002;Boone, Vansteenkiste, Soenens, Van der Kaap-Deeder, & Verstuyf, 2014;Duarte, Pinto-Gouveia, & Rodrigues, 2015;Fennig et al, 2008) and adults (e.g., Bers, Besser, Harpaz-Rotem, & Blatt, 2013;Costa et al, 2015;Duarte, Pinto-Gouveia, & Rodrigues, 2014;Feinson & Meir, 2014;Noordenbos et al, 2014;Shanmugan, Jowett, & Meyer, 2012). In both adolescents and adults, researchers found evidence for the association of self-criticism across multiple forms of DE behavior.…”
Section: Self-criticism Nssi and Dementioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative investigations of the selfcriticism-DE relation began in the 1970s using small samples from clinical and community settings in the United States (Lehman & Rodin, 1989). Research accelerated after 2000 and found support for the relation of these constructs in adolescents (e.g., Berghold & Lock, 2002;Boone, Vansteenkiste, Soenens, Van der Kaap-Deeder, & Verstuyf, 2014;Duarte, Pinto-Gouveia, & Rodrigues, 2015;Fennig et al, 2008) and adults (e.g., Bers, Besser, Harpaz-Rotem, & Blatt, 2013;Costa et al, 2015;Duarte, Pinto-Gouveia, & Rodrigues, 2014;Feinson & Meir, 2014;Noordenbos et al, 2014;Shanmugan, Jowett, & Meyer, 2012). In both adolescents and adults, researchers found evidence for the association of self-criticism across multiple forms of DE behavior.…”
Section: Self-criticism Nssi and Dementioning
confidence: 99%
“…The term self‐harm evokes images of direct actions against one's own body, potentially rendering visible injury. At first glance, behaviors such as overeating, food restriction, or purging seem distinct from directly harmful acts such as cutting, burning, or attempts against one's life; however, researchers have noted conceptual similarities between indirect behaviors (including disordered eating) and direct acts of self‐harm (e.g., Firestone & Seiden, ; Nock, ; Skegg, ). St. Germain and Hooley () observed that certain indirect behaviors may exact extensive physical damage through their sequelae and argued that we should consider these to be indirect forms of self‐harm when certain criteria are met .…”
mentioning
confidence: 99%
“…Self-injurious and suicidal behaviors, however, reported not only strong similarities but also very small differences. Research has indicated that a large number of self-injurers admit that they have also been suicidal (Firestone & Seiden, 1990;Klonsky & Muehlenkamp, 2007;Muehlenkamp & Gutierrez, 2004;Nock et al, 2006). Despite the similarities, research has also revealed obvious differences between the two types of behavior in terms of embodiment, traits, and willingness (Klonsky & Muehlenkamp, 2007;Messer & Fremouw, 2008;Muehlenkamp, 2005).…”
Section: Research-article2015mentioning
confidence: 99%
“…Corre spondingly, adolescents' appraisal of events will be impacted by the degree to which their reasoning capacities have d e veloped. For example, adolescents' perception and understanding of stressors f r e quently differs from that of adults' (Firestone & Seiden, 1990; A.L. Greene, 1988;Greene & Larson, 1991;Phares & Compas, 1990).…”
mentioning
confidence: 99%
“…Stressors that would p r e cipitate suicidal behavior in adults may not show the same or similar causal linkages among adolescents, and the converse also may be true (e.g., Rotheram-Borus & Trautman, 1988;Shaffer, Garland, Gould, Fisher, & Trautman, 1988). In short, stressors that affect adolescents seem to be more closely related to events and emotions whose meanings are idiosyncratically relevant to this period of the life span (Firestone & Seiden, 1990;Greene & Larson, 1991).…”
mentioning
confidence: 99%